RHYMING WORDS IN XUAN DIEU’S POEMS OF LOVE - Đặng Thị Lành (Tạp chí Khoa học Đại học Đà Lạt)
Reduplication is a special part of Vietnamese language. Each reduplicative word itself shows its user’s exquisite and vivid appreciation of social phenomena. Therefore, reduplication is considered an effective means of expression in literature and art, especially in poetry. Each writer or poet has his/her own ways of using reduplication, which forms the writer’s uniqueness and creativity in word forming. This article will focus on rhyming words in Xuan Dieu's poems of love, through which the article reaffirms his distinct creativeness in word usage.